Parental uncertainty about transferring their adolescent with congenital heart disease to adult care. (18th October 2018) - Burström, Åsa; Acuna Mora, Mariela; Öjmyr‐Joelsson, Maria; Sparud‐Lundin, Carina; Rydberg, Annika; Hanseus, Katarina; Frenckner, Björn; Nisell, Margret; Moons, Philip; Bratt, Ewa‐Lena
Abstract: Aims: To study parent's levels of uncertainty related to the transfer from pediatric to adult care in adolescents with congenital heart disease (CHD) and to identify potentially correlating factors. Background: Parents acknowledge that during transition they struggle with finding ways of feeling secure in handing over the responsibility and letting go of control. Well‐prepared and informed parents who feel secure are most likely better skilled to support their adolescent and to hand over the responsibility. Design: A cross‐sectional study. Methods: Overall, 351 parents were included (35% response rate). Parental uncertainty was assessed using a Linear Analogue Scale (0–100). Data were collected between January ‐ August 2016. Potential correlates were assessed using the readiness for transition questionnaire and sociodemographic data. Results: The mean parental uncertainty score was 42.5. Twenty‐four percent of the parents had a very low level of uncertainty (score 0–10) and 7% had a very high level (score 91–100). Overall, 26% of the mothers and 36% of the fathers indicated that they had not started thinking of the transfer yet. The level of uncertainty was negatively associated with the level of perceived overall readiness. Adolescents' age, sex, CHD complexity, and parental age were not related to uncertainty. Conclusion: A wide range in the levels of uncertainty was found. Parents who were less involved in the care, or perceived their adolescent as readier for the transition, felt less uncertain. Still, thirty percent of the parents had not started to think about the transfer to adult care. Abstract : 目的: 目的在于研究父母对于将先天性心脏病(CHD )的青少年从儿科护理转送到成人护理的不确定性水平, 并确定潜在的相关因素。 背景: 这类父母承认, 在过渡期间, 他们很难找到安全的方式来移交责任和放弃控制。 而这类感到安全且有充分准备且知情的父母, 则很有可能很熟练地支持他们的子女且移交责任。 设计: 横断面研究。 方法: 总体而言, 纳入了351名家长(复率为35 % )。采用了先行模拟量表(0至100)来评估父母的不确定性。在2016年1月至8月期间收集了相关数据。采用了过渡准备问卷和社会人口统计数据来评估潜在关联性。 结果: 平均父母不确定性分数为42.5。24 %的父母不确定性很低(得分0 至10), 7 %的父母不确定性很高(得分91至100)。总体而言, 26 %的母亲和36 %的父亲表示他们还没有开始考虑转送。不确定性水平与感知性总体准备程度呈负相关。青少年的年龄、性别、先天性心脏病复杂性和父母年龄与不确定性无关。 结论: 发现了不确定度的范围很广。较少参与护理的父母, 或者这些认为他们的青少年为过渡做好了准备的父母的不确定性减弱。尽管如此, 30 %的父母还没有开始考虑转送至成人护理。